Answer:
(x, y) = (2 2/9, -1 4/9)
Step-by-step explanation:
Equate the values of y and solve for x.
1/4x -2 = -2x +3
(2 1/4)x = 5 . . . . . . . . add 2+2x to both sides
x = 20/9 = 2 2/9 . . . multiply by 4/9
y = -2(2 2/9) +3 = -4 4/9 +3 . . . . substitute for x in the second equation
y = -1 4/9
The solution is x = 2 2/9, y = -1 4/9.
Answer:
Its 280
Step-by-step explanation:
I got it right on A P E X
Answer:
26x-67-x²
Step-by-step explanation:
We are given
![(10x - 3) - (x - 8) {}^{2}](https://tex.z-dn.net/?f=%2810x%20-%203%29%20-%20%28x%20-%208%29%20%7B%7D%5E%7B2%7D%20)
Expanding (x-8)²=x²-16x+64
10x-3-(x²-16x+64)
10x-3-x²+16x-64
26x-67-x²
Answer:
C
Step-by-step explanation:
Square root of 92 is 9.591663047
so round that to 9.59
Answer:
x/6 + 3 = 8
x/6 = 5
x = 30
Step-by-step explanation: